Effects of vanadium on the upper respiratory tract of workers in a vanadium factory. A macroscopic and microscopic study. - Kiviluoto, Markku; Räsänen, Olavi; Rinne, Ari; Rissanen, Martti (Scandinavian Journal of Work, Environment & Health, 1979)
An epidemiologic cross-sectional case-history study on the injurious effects of vanadium was carried out among the workers of a vanadium factory. The upper respiratory tract of 63 male workers exposed to vanadium dust was examined macroscopically and microscopically, and the findings were compared with those of a reference group of workers who were exposed to inert dust only. The groups compared were of similar ages and had similar smoking habits. Nasal smears and sputum cells were studied microscopically, and biopsies for histological study were taken from the nasal mucosa. The biopsies from the vanadium workers showed a significant increase in the number of plasma and round cells, and the histological picture was almost characteristic. There were no increased numbers of secretion eosinophils or other signs indicative of allergic inflammation.
Keywords: cytology; hispathology; macroscopic study; microscopic study; nasal mucosa; upper respiratory tract; vanadium; vanadium dust; vanadium exposure; vanadium factory; worker